P43 Dietary salt intake in Irish adults. (16th November 2010) - Browne, G; Loughrey, M; Harrington, J; Lutomski, J; Fitzgerald, T; Perry, I
Abstract : Objectives: To estimate dietary salt intakes in the Irish population, including variation by age, sex, and measures of obesity. Design: Two cross-sectional studies. Settings and Participants: (i) A nationally representative household sample of 10 364 adults, 62% response rate (SLAN study), (ii) samples of adults aged from 18–81 years (N=599) recruited from the general population, a worksite screening exercise and third level students (Safefood study). Intervention: In both studies, participants underwent physical measurements including height, weight, and waist circumference and in both studies energy intake, macronutrients and dietary sources of salt were estimated by means of a standard Food Frequency Questionnaire. In the SLAN study, random urine samples were obtained from 1207 men and women aged 45 years and older. In the Safefood study, participants provided one 24-h urine collection. Completeness of urine samples were validated using a biomarker, para-amino benzoic acid (PABA). Main Outcome Measures: Estimates of salt intake in Irish adults by age, gender, and levels of obesity and the proportion of total salt intake associated with major food groups. Results: Using SLAN study, random urine samples corrected for urine volume the estimates (mean (SD), median) for salt intake per day in adults aged over 45 years were as follows: men, 10.3 g (5.0), 9.7 g and women, 7.4 g (4.2), 7.1 g. Estimated dietary salt intake (mean (SD), median) based on PABA validated 24 h urine collections was 9.3 g/day (4.1), 8.5 g/day with higher intakes in men: 10.4 g/day (4.3), 9.7 g/day than in women: 7.4 g/day (2.7), 7.1 g/day. 86% of men (95% CI 82% to 90%) and 67% of women (95% CI 60% to 74%) consume more than 6 g salt per day (current tolerable upper limit). Significant variation in salt intake with age was not detected in the PABA validated samples. Dietary salt intake was significantly associated with general and central obesity in both men and women in analyses adjusted for calorie intake. The food groups contributing most to salt intake were cereals, breads, meat, fish and poultry products, which together account for over 50% of salt intakes. Conclusions: Dietary salt intakes in Irish adults remain high, with the majority of the population exceeding the current tolerable upper limit of 6 g per day. At the group level, estimates of salt intake based on random urine samples are similar to those derived from validated 24-h urine collections.